Pre-Service Teachers’ Beliefs, Difficulties and Practices Toward Inquiry-Based Learning: A Mixed-Method Approach - Benitez, John Laurence H.; Quijada, Rachel An; Ragas, Amelyn Mae L.; Gono, Exequiel R. Jr. (European Scientific Journal, ESJ, 2026)
This study aimed to investigate the beliefs of pre-service teachers about Inquiry-based learning, their perceived difficulties, and classroom practices in a classroom setting, which are related to their attitudes towards inquiry-based learning at a private university in Davao City during the school Year 2024-2025. This study employed a convergent mixed-method design involving 92 randomly selected pre-service teachers using stratified random sampling for the quantitative phase. For the qualitative phase, a sample of 15 pre-service teachers was selected through purposive sampling. The 15 samples comprised eight in-depth interviews and seven participants for the focus group discussions. Responses were gathered using a modified survey questionnaire, which included teacher beliefs and attitudes about inquiry-based learning. Moreover, quantitative data were summarized using mean and standard deviation, while qualitative data were analyzed through thematic analysis guided by Creswell’s Procedural Spirals framework. The findings showed strong positive beliefs concerning the effectiveness of inquiry-based learning in enhancing learning for students, particularly in developing their critical thinking and involvement. However, less confidence in classroom practice suggests difficulty with applying that belief into practice, as demonstrated by qualitative themes. The findings suggested that teacher education programs should offer opportunities for training, mentorship, and practical experiences to bridge the gap between motivation and skill in adopting inquiry-based learning to enhance student learning outcomes for pre-service teachers. To support effective implementation, this study recommends targeted professional development focusing on practical inquiry-based learning strategies, mentorship programs to build teacher self-efficacy, integration of practicum experiences, and curriculum reforms aligned with standardized requirements.